Perbaikan Proses Produksi Produk Paper Pallet Berdasarkan Analisis Waste Assessment Model dan Value Stream Analysis Menggunakan Pendekatan Lean Manufacturing pada PT. Kaloka Binangun - Meli Amanda; Sumiharni Batubara (JURNAL TEKNIK INDUSTRI, 2018)
PT. Kaloka Binangun is a packaging company that produces paper pallet products. In the production process of PT. Kaloka Binangun applies a production strategy to make to order. The problem faced by the company today is not achieving production targets. In the production process there are found several waste so that manufacturing lead time is greater than the company's takt time. The process of identifying waste begins using the Waste Relationship Matrix (WRM) and Waste Assessment Questionnaire (WAQ) to determine the percentage of waste that occurs. The results of identification of waste are waste with the 3 biggest ranks, namely, motion (22.96%), transportation (17.53%), and inventory (13.35%). Then the selection of detailed mapping tools is done using Value Stream Analysis Tools (VALSAT). The selected tools are the highest ranking tools, namely Process Activity Mapping (PAM). Implementation of proposed improvements given based on waste analysis is to implement U-Shape Layout, apply 5S, and improve work methods with a map of the right hand and left hand. After implementing improvements, the value of the process cycle efficiency increased from 18.15% to 21.36%. While production output increased from 1425 units to 1724 units.